THE EFFECTIVENESS OF THE INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) IN ADDRESSING HUMAN TRAFFICKING AGAINST INDONESIAN MIGRANT WORKERS IN MALAYSIA POST-COVID-19 - Rizkika Dwi (UNIDA GONTOR, 2021)
This study analyzes the effectiveness of the International Organization for Migration (IOM) as an intergovernmental organization that focuses on migration issues in combating human trafficking of Indonesian migrant workers in Malaysia during the Covid-19 pandemic. IOM basically does not have the authority to eradicate the problem of human trafficking, but because this problem stems from irregular migration, IOM is trying to help the Indonesian government together with various partners to overcome this problem. In its role, IOM established the Counter Trafficking Unit (CTU) which focuses on addressing human trafficking. CTU activities are based on the